Thiomicrorhabdus heinhorstiae sp. nov. and Thiomicrorhabdus cannonii sp. nov.: novel sulphur-oxidizing chemolithoautotrophs isolated from the chemocline of Hospital Hole, an anchialine sinkhole in Spring Hill, Florida, USA. Issue 3 (11th March 2022) - Updegraff, Tatum; Schiff-Clark, Grayson; Gossett, Hunter; Parsi, Sheila; Peterson, Rebecca; Whittaker, Robert; Dennison, Clare; Davis, Madison; Bray, James; Boden, Rich; Scott, Kathleen
Abstract : Two sulphur-oxidizing, chemolithoautotrophic aerobes were isolated from the chemocline of an anchialine sinkhole located within the Weeki Wachee River of Florida. Gram-stain-negative cells of both strains were motile, chemotactic rods. Phylogenetic analysis of the 16S rRNA gene and predicted amino acid sequences of ribosomal proteins, average nucleotide identities, and alignment fractions suggest the strains HH1 T and HH3 T represent novel species belonging to the genus Thiomicrorhabdus . The genome G+C fraction of HH1 T is 47.8 mol% with a genome length of 2.61 Mb, whereas HH3 T has a G+C fraction of 52.4 mol% and 2.49 Mb genome length. Major fatty acids of the two strains included C16 : 1, C18 : 1 and C16 : 0, with the addition of C10:0 3-OH in HH1 T and C12 : 0 in HH3 T . Chemolithoautotrophic growth of both strains was supported by elemental sulphur, sulphide, tetrathionate, and thiosulphate, and HH1 T was also able to use molecular hydrogen. Neither strain was capable of heterotrophic growth or use of nitrate as a terminal electron acceptor. Strain HH1 T grew from pH 6.5 to 8.5, with an optimum of pH 7.4, whereas strain HH3 T grew from pH 6 to 8 with an optimum of pH 7.5. Growth was observed between 15–35 °C with optima of 32.8 °C for HH1 T and 32 °C for HH3 T . HH1 T grew in media with [NaCl] 80–689 mM, with an optimum of 400 mM, while HH3 T grew at 80–517 mM, with an optimum of 80 mM. The name Thiomicrorhabdus heinhorstiae sp. nov. is proposed, and the type strain is HH1 T (=DSM 111584 T =ATCC TSD-240 T ). The name Thiomicrorhabdus cannonii sp. nov is proposed, and the type strain is HH3 T (=DSM 111593 T =ATCC TSD-241 T ).